2014
DOI: 10.1016/j.str.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Actin Binding Surface on Vinculin that Mediates Mechanical Cell and Focal Adhesion Properties

Abstract: SUMMARY Vinculin, a cytoskeletal scaffold protein essential for embryogenesis and cardiovascular function, localizes to focal adhesions and adherens junctions, connecting cell surface receptors to the actin cytoskeleton. While vinculin interacts with many adhesion proteins, its interaction with filamentous actin regulates cell morphology, motility, and mechanotransduction. Disruption of this interaction lowers cell traction forces and enhances actin flow rates. Although a model for the vinculin:actin complex e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 59 publications
10
88
0
Order By: Relevance
“…Interestingly, vinculin directly binds to Factin (Jockusch and Isenberg, 1981;Menkel et al, 1994) and has F-actin-bundling and -capping activities (Le Clainche et al, 2010;Wen et al, 2009). Here, we demonstrated that actin-bindingdeficient vinculin I997A (Thompson et al, 2014) lacks the ability to promote the change in the YAP/TAZ nuclear localization that is dependent on ECM stiffness. Taken together, these observations indicate that vinculin regulates YAP/TAZ at least partly through organization of actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, vinculin directly binds to Factin (Jockusch and Isenberg, 1981;Menkel et al, 1994) and has F-actin-bundling and -capping activities (Le Clainche et al, 2010;Wen et al, 2009). Here, we demonstrated that actin-bindingdeficient vinculin I997A (Thompson et al, 2014) lacks the ability to promote the change in the YAP/TAZ nuclear localization that is dependent on ECM stiffness. Taken together, these observations indicate that vinculin regulates YAP/TAZ at least partly through organization of actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 70%
“…To further gain insight into the relation between actin organization and vinculin, we used the vinculin mutants I997A (denoted IA, deficient in actin binding) and T12 (constitutively active) (Thompson et al, 2014;Cohen et al, 2005). GFP-fused vinculin mutants were expressed in ST2 vinculin-depleted cells (Fig.…”
Section: Vinculin Regulates the Nuclear Localization Of Yap/tazmentioning
confidence: 99%
“…The adapter protein vinculin is an important protein involved in the transduction of mechanical signals (Carisey et al, 2013;Humphries et al, 2007;Thompson et al, 2014). To test the role of vinculin in LIPUS sensing, we first examined whether LIPUS can activate Rac1 in vinculin knockout MEFs (vin -/-MEFs).…”
Section: Sensing Of Lipus Is Mediated Through Vinculin and Its Link Tmentioning
confidence: 99%
“…The link between vinculin and actin has been shown to be critical for the function of vinculin as a transducer of mechanical stimuli (Carisey et al, 2013;Thompson et al, 2014). To test whether this link is also critical for sensing LIPUS, we performed rescue experiments with vin -/-MEFs expressing vinFL…”
Section: Sensing Of Lipus Is Mediated Through Vinculin and Its Link Tmentioning
confidence: 99%
“…Integrins are biochemically linked to a number of cell signaling pathways, but physically they are attached to α-actinin or talin and/ or vinculin, which then links it to the cell's thin filament actin which is a critical regulator of cell shape. This serves as a biochemical and physical link to the scaffold on the outside [64], and cell with mutations causing deficits in the binding capabilities between actin and vinculin demonstrate cell spreading deficits [65].…”
Section: Architecturementioning
confidence: 99%